The role of the Listeria monocytogenes surfactome in biofilm formation - Nika Janež; Blaž Škrlj; Meta Sterniša; Anja Klančnik; Jerica Sabotič (Microbial Biotechnology, 2021)
Summary Listeria monocytogenes is a highly pathogenic foodborne bacterium that is ubiquitous in the natural environment and capable of forming persistent biofilms in food processing environments. This species has a rich repertoire of surface structures that enable it to survive, adapt and persist in various environments and promote biofilm formation. We review current understanding and advances on how L. monocytogenes organizes its surface for biofilm formation on surfaces associated with food processing settings, because they may be an important target for development of novel antibiofilm compounds. A synthesis of the current knowledge on the role of Listeria surfactome, comprising peptidoglycan, teichoic acids and cell wall proteins, during biofilm formation on abiotic surfaces is provided. We consider indications gained from genome‐wide studies and discuss surfactome structures with established mechanistic aspects in biofilm formation. Additionally, we look at the analogies to the species L. innocua, which is closely related to L. monocytogenes and often used as its model (surrogate) organism.